2019
DOI: 10.1111/bph.14813
|View full text |Cite
|
Sign up to set email alerts
|

A novel 2‐aminobenzimidazole‐based compound Jzu 17 exhibits anti‐angiogenesis effects by targeting VEGFR‐2 signalling

Abstract: Background and Purpose Recent development in drug discovery have shown benzimidazole to be an important pharmacophore,. Benzimidazole derivatives exhibit broad‐spectrum pharmacological properties including anti‐microbial, anti‐diabetic and anti‐tumour activity. However, whether benzimidazole derivatives are effective in suppressing angiogenesis and its underlying mechanisms remain incompletely understood. In this study, we aim to characterize the anti‐angiogenic mechanisms of a novel 2‐aminobenzimidazole‐based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…Aorta ring sprouting assay was performed as described previously 32 . Aortic rings isolated from 6- to 8-week-old male Sprague–Dawley rats, then cleaned off periadventitial fat and cut into 1.5 mm size.…”
Section: Methodsmentioning
confidence: 99%
“…Aorta ring sprouting assay was performed as described previously 32 . Aortic rings isolated from 6- to 8-week-old male Sprague–Dawley rats, then cleaned off periadventitial fat and cut into 1.5 mm size.…”
Section: Methodsmentioning
confidence: 99%
“…Target compound 18 also found to reduce lung metastasis of B16F10 melanoma cells in mice models. Molecular docking studies of target compound showed strong binding with in the active site of VEGFR-2 by forming hydrogen bond between nitrogen of benzimidazole with amino acid residue His1026 [63].…”
Section: Vegfr 2 Inhibitorsmentioning
confidence: 99%
“…Dovitinin ( TKI‐258 ) has selective inhibition of FGFR and VEGFR and has shown good efficacy in metastatic renal cell carcinoma in clinical trials (Renhowe et al, 2009). In 2019, Lien et al found that a new type of 2‐aminobenzimidazole analog compound 10 inhibited VEGF‐induced cell proliferation, migration, invasion, and endothelial cell tube formation. Compound 10 inhibited VEGF‐induced microvascular germination in vitro, with IC50 values ranging from 0.3 to 10 µM; and inhibited VEGF or tumor cell‐induced neovascularization in vivo at doses of 2.5 or 5 mg·kg −1 ·day −1 ; it also reduced metastasis in F117 melanoma at doses of 10 mg·kg −1 ·day −1 .…”
Section: Introductionmentioning
confidence: 99%